Graphical abstract from Single-Cell Spatial Analysis Identifies Regulators of Brain Tumor–Initiating Cells - Reza Mirzaei (15306062) (2025)
Graphical abstract. A multi-omics analysis of the glioblastoma tumor microenvironment revealed that biglycan, predominantly expressed by inflammatory BTICs, drives tumor growth. The graphics were generated with Biorender.com.